2010 IEEE Globecom Workshops 2010
DOI: 10.1109/glocomw.2010.5700105
|View full text |Cite
|
Sign up to set email alerts
|

A mobility-aware medium access control protocol for wireless sensor networks

Abstract: Abstract-This paper introduces a light-weight mobility-aware medium access control protocol for wireless sensor networks (MA-MAC). In many respects, the protocol is similar to preamble based, low power listening MAC protocols. It defines a dutycycle to let nodes sleep when they have no packets to transmit. During active communication, the protocol estimates mobility by evaluating the received signal strength of incoming ACK packets and initiates seamless handover by embedding neighbour discovery requests in da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In mobility-aware WSNs, many existing solutions require mobile nodes to constantly evaluate link quality, based on the Received Signal Strength Indicator (RSSI) of acknowledgments received from its temporary next-hop (e.g.,MA-MAC [12] , MX-MAC [3] , MARI-MAC [13] ). Hence, if the mobile node evaluates a too low quality of the link between its current next-hop and itself (i.e., persisting deterioration in the link quality), it initiates a neighborhood discovery process which may lead to a handover situation.…”
Section: Background and Related Workmentioning
confidence: 97%
“…In mobility-aware WSNs, many existing solutions require mobile nodes to constantly evaluate link quality, based on the Received Signal Strength Indicator (RSSI) of acknowledgments received from its temporary next-hop (e.g.,MA-MAC [12] , MX-MAC [3] , MARI-MAC [13] ). Hence, if the mobile node evaluates a too low quality of the link between its current next-hop and itself (i.e., persisting deterioration in the link quality), it initiates a neighborhood discovery process which may lead to a handover situation.…”
Section: Background and Related Workmentioning
confidence: 97%
“…In [9], the authors present MA-MAC (Mobility-Aware Medium Access Control), an extension of the X-MAC [10] protocol. MA-MAC defines two thresholds to handle mobility in WSNs.…”
Section: Related Workmentioning
confidence: 99%
“…Besides MAC and routing protocols holding incoming and outgoing nodes, they should also offer a technique in order to provide a continuous end-to-end communication link. [5] The protocols need to be selected in such a way that they function effectively in both stationary and mobile conditions. It must be conscious about mobility and adaptable to speed of mobile sensors.…”
Section: Mobility Issues Of Wireless Sensor Networkmentioning
confidence: 99%
“…By analyzing previous papers [5], [7] related to mobility aware MAC protocol, it was found that the relay nodes are selected randomly. But there may be a situation that randomly selected relay node may be overloaded or it can be moving, leading to data loss and repeated retransmissions.…”
Section: Problem Identificationmentioning
confidence: 99%
See 1 more Smart Citation